Numerical Simulation of Impulsive Water Waves Generated by Subaerial and Submerged Landslides Incidents in Dam Reservoirs - Vafa Khoolosi; Sedat Kabdaşli (Civil Engineering Journal, 2016)
The water wave generation by a freely falling rigid body is examined in this paper. Landslides on the margins of dam reservoirs may generate large waves that can produce flooding over the banks or overtopping the dam crest. In the present investigation, landslide generated waves are studied using a numerical model based on Navier-Stokes equations. Impulse wave amplitude, period, energy is studied in this work. The effects of bed slope angle on energy conversion from slide into wave are also investigated, and the numerical model we used in this study is the full three dimensional commercial code Flow-3D. Results of the Navier-Stokes model show that waves generated are highly dependent upon the details of slide mechanism and kinematics. Numerical solutions for the velocity fields, pressure distributions, and turbulence intensities in the vicinity of the falling rigid body are also presented. Results show that the general pattern of wave in all cases is the same but the amplitude and period are different. Data analysis shows that the maximum wave crest amplitude in subaerial induced waves is strongly affected by bed slope angle, landslide impact velocity, thickness, kinematics and deformation and by landslide shape.